Aphid Biodiversity under Environmental Change Patterns and Processes - Kindlmann, Pavel; Dixon, A.F.G.; Michaud, J.P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
This book presents completely novel, yet unpublished findings on aphid population dynamics and ecology in the context of recent environmental changes and closely related issues. It can be used as complementary text in any course on population dynamics and ecology of crop pests at undergraduate or graduate levels. The book is intended mainly for graduate students, researchers in crop science, crop protection, agricultural advisors and managers, but it will surely attract attention of many other people interested in insect pests, their biological control and ecology.
Modelling Population Dynamics of Aphids and Their Natural Enemies -- Aphids in a Changing World -- Trends in the Timings of the Start and End of Annual Flight Periods -- Consequences of Climate Change for Aphid-Based Multi-trophic Systems -- Implications of Climate Change for Cereal Aphids on the Great Plains of North America -- Implications of Climate Change for Toxoptera citricida (Kirkaldy), a Disease Vector of Citrus in Florida -- Ecological Factors Influencing Pea Aphid Outbreaks in the US Pacific Northwest -- Temperature, Seasonal Development and Distribution of Insects with Particular Reference to Aphids -- Coccinellids in a Changing World -- Ecological Costs of Alarm Signalling in Aphids.
Keywords: Life sciences; Entomology; Life Sciences; Entomology